Recursos Didácticos en el Aprendizaje de la Matemática en los niños de Inicial II del Centro de Educación Inicial “Juan Samaniego” parroquia Quimiag, cantón Riobamba, provincia de Chimborazo durante el año lectivo 2015-2016. - Granizo Velata, Silvia Catalina (2016)
This research was carried out based on the difficulties in learning mathematics in children of Initial II in the Centro de Education Inicial "Juan Samaniego’. The general objective is to determine the influence of Didactic Resources in Learning of Mathematics, it was established three specific objectives, and then it has the justification and importance of the problem. Moreover, it has the theoretical framework consisting of the research background information, which helped to support this theme; the theoretical foundation refers to the definition, advantages and disadvantages didactic resources, as well as the concept of learning and logical-mathematical relationships in children, so it could make the operationalization of the dependent and independent variables. The methodological framework was done, where the method, types, and research design, population and sample were found. The survey and observation were used as a technique; among the instruments were the questionnaire for teachers and checklist for 24 children, with this information it was developed the analysis and interpretation of results by performing a graphic demonstration, important data to present the conclusions and recommendations of the investigation. Then it is proposed as a possible solution designing a resource guide for the development of in children initial education. It is concluded that this research work is a significant contribution to the educational field, which will help in the academic performance of children.